Pengaruh Diklat dan Motivasi Kerja terhadap Kinerja Pegawai Dinas Pekerjaan Umum Perumahan Rakyat Provinsi Jambi (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
This study aims to determine the effect of training and work motivation on the performance of employees at the Jambi Province Public Works and Public Housing Agency. The background of this research is the decline in employee performance target achievements, which is influenced by budget constraints, limited training opportunities, and low work motivation due to a lack of recognition and organizational support. The research method used is a quantitative method with a descriptive approach and a case study, conducted on employees of the Public Works and Public Housing Agency of Jambi Province. The results show that training has a positive and significant effect on improving employee performance. Training not only serves as a means of instruction but also as a tool for developing employee skills and competencies. Conversely, work motivation has a negative and insignificant effect on employee performance, which is influenced by unmet needs for security, recognition, and encouragement to achieve goals. However, simultaneously, training and work motivation have a positive and significant effect on employee performance. This study concludes that effective training management and appropriate motivational strategies are crucial for improving the performance of employees at the Public Works and Public Housing Agency of Jambi Province.